Phylogenetic Occurrence of the Phenylpropanoid Pathway and Lignin Biosynthesis in Plants - Yao, Tao; Feng, Kai; Xie, Meng; Barros, Jaime; Tschaplinski, Timothy J.; Tuskan, Gerald A.; Muchero, Wellington; Chen, Jin-Gui (Frontiers in Plant Science, 2021)
The phenylpropanoid pathway serves as a rich source of metabolites in plants and provides precursors for lignin biosynthesis. Lignin first appeared in tracheophytes and has been hypothesized to have played pivotal roles in land plant colonization. In this review, we summarize recent progress in defining the lignin biosynthetic pathway in lycophytes, monilophytes, gymnosperms, and angiosperms. In particular, we review the key structural genes involved in p-hydroxyphenyl-, guaiacyl- and syringyl-lignin biosynthesis across plant taxa and consider and integrate new insights on major transcription factors, such as NACs and MYBs. We also review insight regarding a new transcriptional regulator, 5-enolpyruvylshikimate-3-phosphate (EPSP) synthase, canonically identified as a key enzyme in the shikimate pathway. We use several case studies, including EPSP synthase, to illustrate the evolution processes of gene duplication and neo-functionalization in lignin biosynthesis. This review provides new insights into the genetic engineering of the lignin biosynthetic pathway to overcome biomass recalcitrance in bioenergy crops.